Industry 4.0: Transforming E-Commerce and Startup Businesses Through Sustainable Innovation - Febryawan, Aldy; Bintang Diviana Frezita (Optima Science, 2024)
This study explores the transformative impact of Industry 4.0 on e-commerce and startup businesses, with a focus on sustainable innovation. It aims to identify the significant changes brought by Industry 4.0, examine the types of sustainable innovations implemented, and analyze their effects on business performance. Using a qualitative research approach and case study methodology, the research targets e-commerce companies and startups that have adopted Industry 4.0 technologies and sustainable innovations. Data collection involves in-depth interviews with managers and employees, participatory observations, and document analysis, including annual reports and relevant company articles. Data analysis is conducted through data reduction, data display, and conclusion drawing. Validity and reliability are ensured through data source triangulation, member checking, and maintaining an audit trail. The findings reveal substantial changes in e-commerce and startup operations due to Industry 4.0, diverse sustainable innovations adopted, and their positive impacts on efficiency, sustainability, and competitiveness. The study concludes with practical recommendations for e-commerce and startups to enhance the application of Industry 4.0 technologies and sustainable innovations in their business processes. This research provides a comprehensive understanding of how Industry 4.0 and sustainable innovation are driving the transformation of e-commerce and startup businesses.